Proposition of a dynamic steganography system based on the chaos properties and image registration for distributing an encryption key. (14th April 2020) - Rimani, Rachid; Hadj-Said, Naima; Ali-Pacha, Adda
Keys have a crucial role in the security of cryptosystems and their distribution is an important primitive in cryptography. This article presents a new dynamic system of steganography (data hiding) for concealing data in a particular sequence of images intended to regulate in an unlimited time the secure transfer of the key between the different correspondents; the proposed key exchange protocol using an image registration system and a chaotic sequence is comparable to the Diffie-Hellman key exchange protocol. The use of chaos makes it possible to increase the level of confidentiality by sending to the receiver a register which contains parameters of a chaotic sequence; knowing these parameters, the receiver can extract the chaotic sequence. The purpose of using the image registration is to find the transformation between two or several images; these transformations become a tool with the chaotic sequence calculated to recover the key on the receiver side.